2021
DOI: 10.3390/ma15010090
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Silica Fume (SF) on the Rheology, Fluidity, Stability, Time-Varying Characteristics, and Mechanism of Cement Paste

Abstract: In this study, the rheology, fluidity, stability, and time-varying properties of cement paste with different substitute contents of silica fume (SF) were investigated. The result showed that the effects of SF on macro-fluidity and micro-rheological properties were different under different water–cement ratios. The addition of SF increased the yield stress and plastic viscosity in the range of 2.61–18.44% and 6.66–24.66%, respectively, and reduced the flow expansion in the range of 4.15–18.91%. The effect of SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In addition, under a certain WSR, the slurry bleeding rate increases with the increase in coarse aggregate content, resulting in significant stratification of the filling slurry (the upper slurry flowing and filling, and the lower particles precipitating and remaining), and the overall fluidity deteriorates. Therefore, it can be seen that the addition of CG optimizes the grading of the composite system, improves the rheological properties of the slurry, and reduces the plastic viscosity of the slurry, but the overall rheological properties vary with the change in the mass rate of RM/CG of the composite system [48]. Setting time is the key factor to judge whether the filling material can be normally delivered to the hollow area over medium and long distances.…”
Section: Flow and Setting Time Analysismentioning
confidence: 99%
“…In addition, under a certain WSR, the slurry bleeding rate increases with the increase in coarse aggregate content, resulting in significant stratification of the filling slurry (the upper slurry flowing and filling, and the lower particles precipitating and remaining), and the overall fluidity deteriorates. Therefore, it can be seen that the addition of CG optimizes the grading of the composite system, improves the rheological properties of the slurry, and reduces the plastic viscosity of the slurry, but the overall rheological properties vary with the change in the mass rate of RM/CG of the composite system [48]. Setting time is the key factor to judge whether the filling material can be normally delivered to the hollow area over medium and long distances.…”
Section: Flow and Setting Time Analysismentioning
confidence: 99%
“…For decades, studies into supplementary cementitious materials (SCMs) have demonstrated their viability as partial replacements of PC, and for providing technological and environmental benefits [ 2 ]. The most widely used SCMs are fly ash (FA) [ 3 , 4 , 5 ], silica fume (SF) [ 6 , 7 ], or blast furnace slag (BFS) [ 8 , 9 ]. Fluid catalytic cracking catalyst residue (FCC) use has been studied since the late 1990s by various research groups worldwide [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue presents original research results in the following areas: the use of solar panels after the end of their life cycles in the production of cement composites [1]; the radioactivity of building materials in historical buildings [2]; the use of silicon nitride (Si 3 N 4 ) and silicon powder (Si) in the production of briquettes with defined properties [3]; the utilization of by-products of solid waste incineration in concrete production [4]; the comparison of the thermal conductivity of aerated concrete based on fly ash [5]; the utilization of by-products of the incineration of solid municipal waste in the production of foam concrete [6]; the mechanical properties of micropowder cement mortar and engineered cementitious composites (ECC), involving investigations of the use of different methods of processing for municipal solid waste incineration (MSWI) as a mineral admixture [7]; the use of marble dust and blast furnace slag in the production of self-compacting concrete [8]; a new method for the synthesis of insulating aerogel via recycling solid waste coal gangue, which has the potential to reduce the industrial production costs of silica aerogels and realize the high-value-added utilization of solid waste [9]; strength tests and numerical simulations of the Loess modified by desulfurization ash and fly ash [10]; research on the rheological properties of cement paste prepared using silica fume [11]; and, finally, research on the properties of cement paste prepared from superfine basalt powder [12].…”
mentioning
confidence: 99%